Investment and Credit Constraints in Transition Economies: Micro Evidence from Poland, the Czech Republic, Bulgaria and Romania - Jozef Konings; Marian Rizov; Hylke Vandenbussche (Katholieke Universiteit Leuven, LICOS Centre for Transition Economics, 2002)
In this paper we investigate to what extent firm investment in transition countries is sensitive to internal finance. We use accounts data of over 4000 companies in four countries at different stages of transition. We find that firms in Bulgaria and Romania are less sensitive to internal financing constraints, in contrast to firms in Poland and the Czech Republic. A likely explanation is that Bulgaria and Romania, which are the least advanced in the refirms towards market economy, have a stronger persistence of soft budget constraints than in the other two more advanced countries.
Keywords: E22; G32; P21; D21; D92; 330; Investment; financial constraints; soft budget constraint; transition to a market economy; Betriebliche Investitionspolitik; Kreditrationierung; Übergangswirtschaft; Bulgarien; Rumänien; Tschechische Republik; Polen